Baseline Study of Trace Element Concentrations in Sediments of the Intertidal Zone of Amazonian Oceanic Beaches - Vilhena, Jéssica C. E.; Amorim, Ana; Ribeiro, Lourenço; Duarte, Bernardo; Pombo, Maíra (Frontiers in Marine Science, 2021)
Analyzing the presence and quantifying trace elements is of paramount importance to understand natural environmental processes and monitor the degree of anthropogenic disturbance to mitigate impacts already caused. Here, we aimed to establish a baseline of the trace elements profile and concentrations in sandy sediments of intertidal areas of three Amazonian beaches (Brazil). For each beach, sediments were collected from three different sectors (south, center, and north) and five shoreline distance levels (from the high- to the low-water mark), totalizing 15 samples per beach. The concentration of the different trace elements (Mg, Al, P, S, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Br, Rb, Sr, Y, Zr, Cd, Sn, I, Hg, and Pb) was determined by Total reflection X-ray Fluorescence spectrometry. Sediment was also characterized for its grain size, organic matter, and pH. To assess possible enrichment due to anthropogenic activities we compared trace element levels with the values for the Earth’s crust and calculated pollution indexes: Geoaccumulation index (Igeo), Ecological risk index (RI), Contamination Factor (CF), pollution load index (PLI), and sediment quality guideline (SQG) Threshold Effects Level (TEL) and Probable Effects Level (PEL). Individual trace metal concentrations did not vary significantly between beaches, sectors, or sample levels, evidencing a homogeneity of trace elements composition and concentrations across this environment. Igeo indicated 62.2% of the sampling stations uncontaminated, 20.0% from uncontaminated to moderately contaminated, and 4.44% (2 sampling stations) strongly contaminated, the same 2 areas classified as high ecological risk by RI. Most of the sampling points presented low CF. Cadmium and Hg were the only elements that showed moderate to very high values of CF. According to the SQGs, 77.7% and 8.8% of the sampling points presented values above the moderate threshold effect level (SQG-TEL) and probable effect level (SQG-PEL), respectively. All points were classified as non-polluted according to the PLI. Our results show that the three beaches present safe levels of almost of the elements demonstrating the good state of preservation. Most of the indexes classified the sampling points as non-polluted, except for Cd and Hg in a few specific sampling points.